Variability of Carcass Traits of Local Poultry Populations of Gallus gallus Species of Benin - Tougan, U.P.; Dahouda, M.; Salifou, C.F.A.; Ahounou, S.G.; Kpodekon, M.T.; Mensah, G.A.; Kossou, D.N.F.; Amenou, C.; Kogbeto, C.E.; Thewis, A.; Youssao , I.A.K. (International Journal of Poultry Science, 2013)
The local poultry population of Benin is composed of various ecotypes including chickens Holli, Sahoue, Fulani, North and South. To better characterize them, our study aims to assess their carcass traits according to genetic type, breeding system and slaughter age. Thus, 260 chickens of which 52 chickens of each ecotype were divided in two lots and reared respectively under traditional and improved breeding system. For each breeding system, 26 cockerels of each ecotype were slaughtered at 20, 24 and 28 weeks old for carcass traits study. The results show that the live weight, the carcass weight, the weight of the cuts of thigh-drumsticks and wings of Holli chickens were the highest (p0.05) but heavier (p